The Use of Digital-Based Media in Speech Writing Learning for Grade VIII Students at SMP Negeri 1 Pulubala - Novita Bangi; Sayama Malabar; Muslimin (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Based on the above research, the objectives of this study are (1) to describe the design of digital-based learning media in teaching speech writing to eighth-grade students of SMP Negeri 1 Pulubala, (2) to describe the use of digital-based media in teaching speech writing to eighth-grade students of SMP Negeri 1 Pulubala, and (3) to describe the inhibiting factors in the use of digital-based media in teaching speech writing to eighth-grade students of SMP Negeri 1 Pulubala. The research method used is descriptive qualitative. Data collection techniques used interviews, observation, and documentation. The subjects in this study were 27 teachers and eighth-grade students and the object of this study was the results of students' speech writing using digital media. The aspects assessed in writing speech texts were the appropriateness of the speech text content, content organization, accuracy of diction, and accuracy of the speech text structure. Based on the results of the study, the design and use of digital-based learning media such as PowerPoint and YouTube in teaching speech writing have been effective because they are able to present material in a structured manner, provide concrete examples, and increase student understanding, motivation, and activeness. Digital media also supports varied learning strategies and assessment of learning outcomes. However, its use still faces challenges such as limited devices and internet access, necessitating improvements in facilities and infrastructure to optimize learning.